Exploring the structural and optical properties of low dimensional halide perovskite-like compounds at extreme conditions - Padrón Gómez, Mayra Alexandra (2023)
Low dimensional Metal Halide Perovskite like (MHPs) compounds have emerged as promising materials for various optoelectronic applications, including photodetectors and solar cells. These compounds feature a metal halide octahedron as the fundamental structural unit, crucial in dictating their optoelectronic and chemical properties. To further investigate and harness their unique potential, researchers have explored extreme conditions, such as low temperatures and high pressures, to induce structural changes and explore their impact on electronic and o ptical properties uncovering novel physical properties and establishing a comprehensive understanding of the structural property relationship. One example is the zero dimensional bromide hexa Bromo bismuthate {[(CH3)2NH2]+}4Br−.[BiBr6]3-, which at low temperature (T < 100 K) and without involving a structural phase transition, the intriguing octahedra distortion produces a photoluminescence (PL) state changing its optical properti es. On the other hand, the two dimensional CsPb2Cl5 undergoes two structural phase transitions at high pressures, where the low-pressure phase PI : I4/mcm transforms into phase PII: I4/m at PcI-II=1.60 GPa, and subsequently changes to phase PIII:C2 at PcII-III = 5.16 GPa. On the other hand, an occupational disorder was observed in the family of CsPb2(Br1-xIx)5 , where both Br and I ions occupy the same position at 16l sites . Regarding PL properties, the iodine substitution increases PL intensity and modifies the energy emission, demonstrating a redshift of the PL center. Finally, the low temperature Raman spectroscopy and PL of the CsPb2Br5 compound provided valuable insights into the origin of its photoluminescence. The evolution of the photoluminescence spectra at low temperat ures reveals an intriguing increase in emission intensity and the emergence of a dual emission band beyond 60 K. Specifically, the narrow photoluminescence observed at room temperature can be attributed to the radiative recombination of free excitons. In contrast, the broad emission observed at low temperatures is ascribed to the presence of self trapped excitons (STE). In this context, the results of the structural property relations in past metal halide perovskite like pave the way for developing new and improved devices and technologies for different applications.